Win - Coben, Harlan, 1962- (2021)
"Over twenty years ago, the heiress Patricia Lockwood was abducted during a robbery of her family's estate, then locked inside an isolated cabin for months. Patricia escaped, but so did her captors - and the items stolen from her family were never recovered. Until now. On the Upper West Side, a recluse is found murdered in his penthouse apartment, alongside two objects of note: a stolen Vermeer painting and a leather suitcase bearing the initials WHL3. For the first time in years, the authorities have a lead - not only on Patricia's kidnapping, but also on another FBI cold case - with the suitcase and painting both pointing them toward one man. Windsor Horne Lockwood III - or Win, as his few friends call him - doesn't know how his suitcase and his family's stolen painting ended up with a dead man. But his interest is piqued, especially when the FBI tells him that the man who kidnapped his cousin was also behind an act of domestic terrorism - and that the conspirators may still be at large. The two cases have baffled the FBI for decades, but Win has three things the FBI doesn't: a personal connection to the case; an ungodly fortune; and his own unique brand of justice."--Provided by publisher
Series information from www.goodreads.com
In English
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Cold cases (Criminal investigation) -- Fiction; Kidnapping -- Fiction; Theft -- Fiction; Justice -- Fiction; Thrillers (Fiction); Detective and mystery fiction